PEMBERDAYAAN ANAK UNTUK MENINGKATKAN MOTIVASI BELAJAR DENGAN MODEL BERMAIN, BERKREASI DAN LITERASI (BBL) DI DESA KARANG INDAH - Baharuddin, Baharuddin; Resky, Muhammad; Afkar, Muhammad Syakhil; Lusiana, Lusiana (DEVOSI, 2025)
Motivating elementary school children to learn is often a challenge in education. This community service project aims to increase elementary school children's motivation to learn through a more enjoyable and holistic approach by combining play, creative activities, and literacy in a program called the BBL Model (Play, Creative Activities, Literacy). This community service project uses a participatory approach. The activities were carried out at the Karang Indah Village Reading Park in three stages, namely the preparation stage, which included needs analysis, program development, and coordination. The implementation stage included the location of activities, tools and materials, and the BBL event series. The third stage was evaluation and assessment, which included discussion and interaction, as well as measurement of results. The results of this community service showed a significant increase in the children's motivation to learn in Karang Indah Village. First, there was an increase in enthusiasm, with children showing high interest and active participation in learning activities integrated with game elements. Second, there was an increase in literacy skills, including the children's reading and writing skills, which were strengthened through fun literacy activities. Third, an increase in creativity, with children being more active in creating through drawing and craft activities, which supports cognitive development. This community service project demonstrates the importance of local and national education policies considering more interactive and enjoyable learning methods, which can increase student interest and engagement. This service has implications for the development of sustainable programs to continue supporting children's educational development, especially in areas with limited resources, and to improve access to educational resources to support more effective learning activities.